Humor atau Superioritas? Mengupas Motif Pelaku Catcalling Melalui Teori Dominasi Sosial - Aulia Maulidina; Nabila Regita Putri Mustafa; Tsania Rahima Abqoriyyin; Dea Anindya; Ade Maulidya Marantika; Nabila Hasna Ramadhini; Rahmi Fauzie; Ermina Istiqomah; Risna Febriani; Siti Raiyati (Universitas Ciputra Surabaya, 2026)
The phenomenon of catcalling is a form of verbal sexual harassment that is increasingly prevalent. Victims of catcalling tend to feel disturbed and uncomfortable rather than perceiving it as a compliment from the perpetrators. This study aims to explore the perceptions of perpetrators behind the act of catcalling through Social Dominance Theory (SDT). The research employs a qualitative approach with a single instrumental case study design, using purposive sampling techniques. Data collection was conducted through semi-structured interviews with two participants who met the specified criteria. The findings of the study reveal two major themes: perceptions underlying catcalling, which include normalization of the behavior, and the role of social dominance in catcalling, where men perceive themselves as dominant in social environments and destined to be superior to women. This gender inequality fosters sexism and tolerance toward sexual harassment.